Assessment of the latest NGS enrichment capture methods in clinical context - García-García, Gema (Sci Rep, 2016)
Enrichment capture methods for NGS are widely used, however, they evolve rapidly and it is necessary to periodically measure their strengths and weaknesses before transfer to diagnostic services. We assessed two recently released custom DNA solution-capture enrichment methods for NGS, namely Illumina NRCCE and Agilent SureSelect(QXT), against a reference method NimbleGen SeqCap EZ Choice on a similar gene panel, sharing 678 kb and 110 genes. Two Illumina MiSeq runs of 12 samples each have been performed, for each of the three methods, using the same 24 patients (affected with sensorineural disorders). Technical outcomes have been computed and compared, including depth and evenness of coverage, enrichment in targeted regions, performance in GC-rich regions and ability to generate consistent variant datasets. While we show that the three methods resulted in suitable datasets for standard DNA variant discovery, we describe significant differences between the results for the above parameters. NimbleGen offered the best depth of coverage and evenness, while NRCCE showed the highest on target levels but high duplicate rates. SureSelect(QXT) showed an overall quality close to that of NimbleGen. The new methods exhibit reduced preparation time but behave differently. These findings will guide laboratories in their choice of library enrichment approach.